Islamic Bank Customers’ Categorization of Cognitive Process Regarding Usury: A Case Study in Bank Syariah Indonesia Manado - Telsy Fratama Dewi Samad; Ahmad Saifulloh (Millah: Journal of Religious Studies, 2022)
Although previous studies on usury have been conducted, the focus on customers’ knowledge of usury was limited. This study aimed to analyze Islamic bank customers’ cognitive process regarding usury and to analyze the differences between Muslim and non-Muslim customers’ perspectives regarding usury practice in the bank. The study could be categorized as qualitative because it used qualitative data in the form of interview results. Furthermore, it used a case study approach with Bank Syariah Indonesia Manado as the location. Twenty customers of the bank, ten of them Muslims and ten other non-Muslims, were selected as participants using a convenience sampling method. They were interviewed using the Zoom application to collect data on their knowledge regarding usury and Islamic banks. Anderson and Krathwohl’s categories of the cognitive process were used to categorize participants’ responses. The results showed that all customers attained level 1 (remember) and level 2 (understand) usury and only four of them attained level 3 (apply) based on Anderson and Krathwohl’s categorization. It implied that only four of ten Muslim participants become customers of the Islamic bank because of their belief in the bank’s status as a usury-free financial institution. Other findings suggested that all customers were in the same opinion that money lending practiced by the loan sharks should be categorized as usury, while not all customers viewed money lending by the current banking industry as usury.